An evaluation of operation and creep life of stationary gas turbine engine - Eshati, Samir (Cranfield University, 2012)
During operation, gas turbine components undergo various types of timedependent degradation due to high temperatures and mechanical loading. In the case of stationary GT engines for mechanical power, creep failure mechanism problems are a very common cause of mechanical failure that significantly reduces component life. The magnitude of the adverse effect is highly dependent on the operating conditions and design parameter of the components. Against this background, the research programme was aimed at achieving a better scientific understanding of the major reasons for creep failure. This would allow mechanical equipment to keep running free creep problem for longer. Therefore, the aim of this research was to develop an analytical life model capable of assessing the influence of humidity on the turbine blade heat transfer and cooling processes considering the engine design parameters, operating conditions and working environment which, in turn, affect blade creep life. The whole cooled blade row is regarded as heat exchanger with convective/film cooling and a thermal barrier coating. The approach is based on an engine performance model, heat transfer models and the change of properties of moist air as a function of water to air ratio (WAR). The changes of fluid properties due to the presence of water vapour were not only considered through a variation of the specific heat, the ratio of major specific heats and gas constant, but also with the variation of density, Reynolds number, Nusselt number and other related parameters. Cont/d.